Nano frosted agent, preparation method thereof, composition and application of nano frosted agent in paper-like film

By using nano-frosting agent composed of hollow TPU fiber particles and in situ deposited growing silica layer in paper-like film, the paper-like film has solved the problem of both damping, touch, wear resistance and optical properties, and improved the Experience and lifespan, and reduce production costs.

CN119242265AActive Publication Date: 2025-01-03JIANGSU KANGHUI NEW MATERIALS TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411775207.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing paper-like films are difficult to fully consider the damping feeling, touch feeling, wear resistance and optical properties, resulting in poor user experience and short life.

Method used

Using nano-frosting agent composed of hollow TPU fiber particles and in-situ deposition grown silica layer, the double-layer airbag structure is formed in a paper-like film to improve damping sense and elasticity, and through nano-frosting agents of different particle sizes Distribution improves touch and extends service life.

Benefits of technology

It has achieved improvements in damping, touching and wear resistance of paper-like films, extending service life, while maintaining good optical performance, providing a more natural writing experience and lower production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic materials, and relates to a nanometer frosted agent, a preparation method thereof, a composition and an application of the nanometer frosted agent in a paper-like film. The nanometer frosted agent is composed of hollow TPU fiber particles and a silicon dioxide layer which grows on the outer wall of the hollow TPU fiber particles in an in-situ deposition mode. The nano frosted agent composition is prepared from nano frosted agents with different particle size ranges according to a specific proportion; the preparation method of the nano frosted agent comprises the following steps: preparing hollow TPU fiber particles, preparing a solution A containing a silicon source, adding the hollow TPU fiber particles into the solution A, reacting, and then carrying out post-treatment. According to the application, the nano frosted agent or the nano frosted agent composition is prepared into an extrusion type high-wear-resistance and high-resilience paper film. According to the invention, the comprehensive improvement of the paper-like film in four aspects of damping sense, touch sense, wear resistance and optical performance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic materials and relates to a nano-abrasive agent and a preparation method and a composition thereof and application in a paper-like film. Background Art

[0002] In recent years, with the rapid development of electronic writing technology, paper-like films have attracted widespread attention as a key material for improving the writing experience on electronic screens. Paper-like films are designed to simulate the writing feel of paper and provide users with a more natural and comfortable writing experience.

[0003] Damping sense is one of the important indicators of paper-like film in simulating the writing experience of paper. By providing appropriate damping sense, paper-like film simulates the friction when writing on paper, allowing users to feel a more realistic writing experience. Touch is another key factor that affects the user experience of paper-like film. The ideal paper-like film should not only have sufficient damping sense, but also simulate the softness and elasticity of paper in touch, so that users feel comfortable when writing. Wear resistance is also an aspect that cannot be ignored in the application of paper-like film. Since paper-like film needs to withstand frequent writing friction, its wear resistance is directly related to its service life. In addition, optical performance is also one of the important indicators for evaluating the quality of paper-like film. Good optical performance can ensure that the paper-like film does not affect the display effect of the electronic screen while providing a writing experience.

[0004] However, the existing paper-like films still have many deficiencies in performance, especially in terms of damping, touch, wear resistance and optical performance. For example, the patent application CN115369684A discloses a hardening layer coating liquid and an antibacterial paper-like film. Although a large amount of silicon dioxide is added to provide a damping feeling, this method will result in a stiff touch, and after long-term use, the silicon dioxide will wear, affecting the damping feeling and optical performance.

[0005] Therefore, developing a paper-like film material that can simultaneously meet the requirements of damping, touch, wear resistance and optical performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a nano-abrasive agent and a preparation method and composition thereof and application in paper-like films.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A nano-abrasive agent consists of hollow TPU fiber particles and a silicon dioxide layer in-situ deposited and grown on the outer wall of the nano-abrasive agent.

[0009] As the preferred technical solution:

[0010] In the nano-abrasive agent as described above, the content of silicon dioxide in the nano-abrasive agent is 50-60wt%.

[0011] As described above, the nano-abrasive agent has a particle size of less than 0.5 μm, the inner diameter of the hollow TPU fiber particles is 0.1-0.2 μm and the wall thickness is 0.05 μm, and the thickness of the silicon dioxide layer is 0.05-0.1 μm; the nano-abrasive agent of this size is recorded as nano-abrasive agent A.

[0012] A nano-abrasive agent as described above, the particle size of the nano-abrasive agent is greater than or equal to 0.5 μm and less than 1 μm, the inner diameter of the hollow TPU fiber particles is 0.2-0.4 μm and the wall thickness is 0.1 μm, and the thickness of the silicon dioxide layer is 0.1-0.2 μm; the nano-abrasive agent of this size is recorded as nano-abrasive agent B.

[0013] A nano-scrubber as described above, the particle size of the nano-scrubber is greater than or equal to 1 μm and less than 10 μm, the inner diameter of the hollow TPU fiber particles is 0.4-4 μm and the wall thickness is 0.1-1 μm, and the thickness of the silicon dioxide layer is 0.2-2 μm; the nano-scrubber of this size is recorded as nano-scrubber C.

[0014] A nano-scrubber as described above, the particle size of the nano-scrubber is greater than or equal to 10μm and less than 20μm, the inner diameter of the hollow TPU fiber particles is 3-6μm and the wall thickness is 1.5-3μm, and the thickness of the silicon dioxide layer is 2-4μm; the nano-scrubber of this size is recorded as nano-scrubber D.

[0015] A nano-scrubber as described above, the particle size of the nano-scrubber is greater than or equal to 20μm and less than or equal to 25μm, the inner diameter of the hollow TPU fiber particles is 6-7μm and the wall thickness is 3-4μm, and the thickness of the silicon dioxide layer is 4-5μm; the nano-scrubber of this size is recorded as nano-scrubber E.

[0016] The present invention also provides a nano-abrasive composition, which consists of 30-50wt% of nano-abrasive A, 20-25wt% of nano-abrasive B, 15-20wt% of nano-abrasive C, 10-15wt% of nano-abrasive D, and 5-10wt% of nano-abrasive E.

[0017] The present invention also provides a method for preparing a nano-abrasive agent as described in any one of the above items, comprising the following steps:

[0018] (a) Preparation of hollow TPU fiber particles;

[0019] (b) dissolving a silicon source in an acidic solution to obtain a solution A;

[0020] (c) The hollow TPU fiber particles are added to solution A, and after adding alkali, the mixture is reacted at 60° C. under stirring for 2-6 hours to obtain solution B. Solution B is post-treated (filtration, pure water washing, and drying) to obtain a nano-abrasive.

[0021] As the preferred technical solution:

[0022] In the method described above, step (a) specifically comprises: dissolving TPU particles in N,N-dimethylacetamide to obtain a spinning solution with a concentration of 10-30%, and using a hollow fiber spinneret and a wet spinning process to perform spinning and then cutting to obtain hollow TPU fiber particles.

[0023] In the method as described above, in step (b), the silicon source is one or more of tetraethyl silicate, tetramethyl silicate, methyltrimethoxysilane, ethyltriethoxysilane and sodium silicate, the acidic solution is hydrochloric acid solution and / or acetic acid solution, and the pH value of solution A is 2-4.

[0024] In the method as described above, in step (c), the mass ratio of the hollow TPU fiber particles to solution A is 1-2:8-9, the alkali is one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide, and the mass of the alkali is 20-70% of the mass of the silicon source.

[0025] The present invention also provides an extruded high-wear-resistant and high-resilient paper film, comprising an upper surface layer, a base layer and a lower surface layer arranged in sequence from top to bottom; the upper surface layer and the lower surface layer contain additives, and the additive is a nano-abrasive as described in any of the above items or a nano-abrasive composition as described above. When the additive is a nano-abrasive composition, when the larger particles in the system are slightly worn, the smaller particles have not yet begun to participate in the wear, so its overall friction resistance is stronger. At the same time, due to the distribution of different particle sizes in the system, this helps to disperse the force, thereby greatly reducing the wear of the nano-abrasive.

[0026] As the preferred technical solution:

[0027] As described above, the extruded high wear-resistant and high resilience paper film, the upper surface layer or the lower surface layer is composed of 65-85wt% of PET and the remainder of additives; the base layer is composed of 50-62wt% of PET, 30-35wt% of TPU, 5-10wt% of compatibilizer (polyolefin elastomer POE, maleic acid rod grafted compatibilizer TPU-G-MAH, etc.) and the remainder of plasticizer (ethylene terpolymer).

[0028] As described above, the thicknesses of the upper surface layer, base layer and lower surface layer of the extruded high wear-resistant and high resilience paper film are 0.08-1.2 mm, 0.2-0.24 mm and 0.08-1.2 mm respectively; the haze of the extruded high wear-resistant and high resilience paper film is 2.1-2.7%, the tensile resilience is 96.2-99.8%, the elongation at break is 320-351%, the light transmittance is 92.68-95.55%, the friction resistance is 800-1600 times, and the dynamic friction coefficient is 0.39-0.46.

[0029] The present invention also provides a method for preparing an extruded high-wear-resistant and high-rebound paper film as described in any one of the above items, comprising the following steps:

[0030] (A) melt-blending and granulating the raw materials corresponding to the upper surface layer to obtain a modified slice a, melt-blending and granulating the raw materials corresponding to the base layer to obtain a modified slice b, and melt-blending and granulating the raw materials corresponding to the lower surface layer to obtain a modified slice c;

[0031] (B) melt-extrude the modified slice a, the modified slice b, and the modified slice c through an extruder, pass through a filter, a melt metering pump, a distributor, and a multi-layer co-extrusion die, and cool on a cooling roller to obtain a thick slice;

[0032] (C) The thick sheet is sequentially subjected to longitudinal stretching (stretching temperature is 80-100°C, stretching ratio is 3-3.6 times), transverse stretching preheating (temperature is 80-120°C), transverse stretching (stretching temperature is 100-130°C, stretching ratio is 3.1-4 times), drying and curing (temperature is 200-240°C), heat setting, and cooling to obtain an extruded high wear-resistant and high resilience paper film.

[0033] Principle of the invention:

[0034] The nano-abrasive agent of the present invention contains silicon dioxide, so the paper-like film to which the nano-abrasive agent is added has a stronger damping feeling.

[0035] The nano-abrasive agent of the present invention is a double-layer airbag structure with hollow TPU fiber particles as the inner shell and a silicon dioxide layer as the outer shell. After being added to a paper-like film, the elastic properties of the paper-like film can be improved. When a certain position of the paper-like film is subjected to a large external force, the external force will be dispersed in all directions through the double-layer airbag structure, achieving a certain buffering effect on the hand. After the external force disappears, the film surface will be restored to its original state. In addition, by adding nano-abrasive agents of different particle sizes, the different damping sensations caused by different forces during the writing process can be effectively improved. Therefore, the paper-like film with the addition of the nano-abrasive agent can improve the tactile feel of writing.

[0036] In the nano-abrasive agent of the present invention, since the silica layer is in-situ deposited and grown on the outer wall of the hollow TPU fiber particles, the hollow TPU fiber particles provide better support for the external silica layer, disperse the force on the silica during contact, reduce the wear of the silica, and increase the service life of the paper-like film.

[0037] The nano-abrasive agent of the present invention acts as an opening agent in the production process of the paper-like film, which saves costs and also has a smaller impact on the light transmittance of the overall paper-like film.

[0038] Beneficial effects:

[0039] The nano-abrasive agent of the present invention is a double-layer airbag structure with hollow TPU fiber particles as the inner shell and a silicon dioxide layer as the outer shell, so that the paper-like film can provide a better damping feeling when writing, simulating the friction of paper when writing, while maintaining a soft and elastic touch, so that users can feel a more natural and comfortable experience when writing;

[0040] Since the silica layer is in-situ deposited and grown on the outer wall of the hollow TPU fiber particles, it provides good support for the silica layer and effectively disperses the force, thereby significantly reducing wear and tear and extending the service life of the paper-like film.

[0041] Nano-abrasives are used as opening agents in paper-like films, which not only reduces production costs, but also has little impact on the light transmittance of the overall paper-like film, ensuring that the paper-like film does not affect the display effect of the electronic screen while providing an excellent writing experience. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:

[0044] Haze: Tested in accordance with GB / T 2410-2008 standard.

[0045] Tensile resilience: The test was conducted using an ACTS-T300 fully automatic tensile testing machine. The specific steps were as follows: 10 cm long paper-like film and PET (as reference material, the manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model FG720) were cut, and both ends of the two samples were clamped in the fixture of the tensile testing machine to ensure that the samples remained in the correct position during the test. Then, a tensile test was conducted and the rebound length was measured. The tensile resilience was calculated according to the following formula:

[0046] Tensile resilience (%) = (rebound length - initial length) / initial length × 100%;

[0047] The sample was subjected to 50 parallel tensile tests, and the average value was taken as the final springback result.

[0048] Elongation at break: tested in accordance with GB / T 528-2009 standard, with a tensile speed of 100 mm / min.

[0049] Light transmittance: Tested in accordance with GB / T 2410-2008 standard.

[0050] Friction resistance times: Kunshan Jingjia Instrument A20-339 was used to test according to JISK-5600-1999 standard. The specific process is: Use 0000# steel wool to wipe the surface of the paper film back and forth under a constant load of 1000gf / cm² to detect the maximum limit number of times that scratches appear on the film surface.

[0051] Dynamic friction coefficient: The test is conducted in accordance with JISK-5600-1999 standard. During the test, a felt with a side length of 5 cm is used, and a constant load of 200 g is applied thereto. Then, the felt is pulled at a constant speed on the surface of the paper-like film, and the dynamic friction coefficient is recorded and calculated.

[0052] Example 1

[0053] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0054] (1) Preparation of raw materials;

[0055] TPU particles: manufacturer is Wanhua Chemical Group Co., Ltd., model number is WHT-1172IC;

[0056] N,N-dimethylacetamide;

[0057] Silicon source: a mixture of tetraethyl silicate and tetramethyl silicate in a mass ratio of 1:1;

[0058] Acidic solution: hydrochloric acid aqueous solution, concentration is 20wt%;

[0059] Alkali: sodium hydroxide;

[0060] (2) Preparation of nano-abrasives;

[0061] (2.1) dissolving TPU particles in N,N-dimethylacetamide to obtain a spinning solution with a concentration of 10%, and cutting after spinning using a hollow fiber spinneret and a wet spinning process to obtain hollow TPU fiber particles;

[0062] (2.2) Dissolve the silicon source in an acidic solution and stir at 20°C until no stratification occurs to obtain a solution A having a pH value of 2;

[0063] (2.3) adding the hollow TPU fiber particles to solution A, adding alkali, stirring and reacting at 60°C for 2 hours to obtain solution B, and post-treating solution B to obtain a nano-abrasive;

[0064] In steps (2.1) to (2.3), the mass ratio of the hollow TPU fiber particles to solution A is 1:9, and the mass of the alkali is 20% of the mass of the silicon source.

[0065] The final nano-scrubber is composed of hollow TPU fiber particles and a silica layer in-situ deposited and grown on its outer wall. The silica content in the nano-scrubber is 50wt%; the particle size of the nano-scrubber is less than 0.5μm, the inner diameter of the hollow TPU fiber particles is 0.1-0.2μm and the wall thickness is 0.05μm, and the thickness of the silica layer is 0.05-0.1μm.

[0066] Comparative Example 1

[0067] A method for preparing a nano-abrasive is basically the same as that of Example 1, except that the TPU particles are replaced with PP (polypropylene) particles (manufacturer: Formosa Chemical & Plastics Corporation, Taiwan, China, brand number S1005).

[0068] The final nano-abrasive agent is composed of hollow PP particles and a silicon dioxide layer in situ deposited and grown on its outer surface; the particle size of the nano-abrasive agent is less than 0.5 μm, the inner diameter of the hollow PP particles is 0.1-0.2 μm and the wall thickness is 0.05 μm, and the thickness of the silicon dioxide layer is 0.05-0.1 μm.

[0069] Comparative Example 2

[0070] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0071] (1) Preparation of raw materials;

[0072] Ammonium chloride;

[0073] Methanol aqueous solution: concentration 10wt%;

[0074] Silicon source: a mixture of tetraethyl silicate and tetramethyl silicate in a mass ratio of 1:1;

[0075] Acidic solution: hydrochloric acid aqueous solution, concentration is 20wt%;

[0076] Alkali: sodium hydroxide;

[0077] (2) Preparation of nano-abrasives;

[0078] (2.1) dissolving ammonium chloride in a methanol aqueous solution to obtain an ammonium chloride-methanol aqueous solution with a concentration of 10 wt%;

[0079] (2.2) Dissolve the silicon source in an acidic solution and stir at 20°C until no stratification occurs to obtain a solution A having a pH value of 3;

[0080] (2.3) Add ammonium chloride-methanol aqueous solution to solution A, stir and react at 0°C for 3 h, then add alkali, stir and react at 60°C for 6 h, then heat to 90°C and keep warm for 3 h to obtain solution B, and post-treat solution B (suction filtration, pure water washing, drying) to obtain a nano-abrasive agent;

[0081] In steps (2.1) to (2.3), the mass ratio of the ammonium chloride-methanol aqueous solution to solution A is 1:1, and the mass of the alkali is 40% of the mass of the silicon source.

[0082] The nano-scrubber finally prepared is hollow silicon dioxide; the particle size of the nano-scrubber is less than 0.5 μm, and the wall thickness is 0.2-0.4 μm.

[0083] Comparative Example 3

[0084] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0085] (1) Preparation of raw materials;

[0086] Silicon source: a mixture of tetraethyl silicate and tetramethyl silicate in a mass ratio of 1:1;

[0087] Acidic solution: hydrochloric acid aqueous solution, concentration is 20wt%;

[0088] Alkali: sodium hydroxide;

[0089] (2) Preparation of nano-abrasives;

[0090] (2.1) Dissolve the silicon source in an acidic solution and stir at 20°C until no stratification occurs to obtain a solution A with a pH value of 3;

[0091] (2.2) After adding alkali to solution A, the mixture was stirred and reacted at 60° C. for 6 h to obtain solution B. Solution B was post-treated (suction filtration, pure water washing, and drying) to obtain a nano-abrasive. The mass ratio of alkali to solution A was 1:1.

[0092] The nano-scrubber finally prepared is solid silicon dioxide; the particle size of the nano-scrubber is less than 0.5 μm.

[0093] Example 2

[0094] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0095] (1) Preparation of raw materials;

[0096] TPU particles: manufacturer is Wanhua Chemical Group Co., Ltd., model number is WHT-1172IC;

[0097] N,N-dimethylacetamide;

[0098] Silicon source: methyltrimethoxysilane;

[0099] Acidic solution: acetic acid aqueous solution, concentration 20wt%;

[0100] Alkali: potassium hydroxide;

[0101] (2) Preparation of nano-abrasives;

[0102] (2.1) dissolving TPU particles in N,N-dimethylacetamide to obtain a spinning solution with a concentration of 20%, and using a hollow fiber spinneret and a wet spinning process to perform spinning and then cutting to obtain hollow TPU fiber particles;

[0103] (2.2) Dissolve the silicon source in an acidic solution and stir at 25°C until no stratification occurs to obtain a solution A having a pH value of 2.5;

[0104] (2.3) adding the hollow TPU fiber particles to solution A, adding alkali, stirring and reacting at 60°C for 3 hours to obtain solution B, and post-treating solution B to obtain a nano-abrasive;

[0105] In steps (2.1) to (2.3), the mass ratio of the hollow TPU fiber particles to solution A is 1:9, and the mass of the alkali is 40% of the mass of the silicon source.

[0106] The final nano-scrubber is composed of hollow TPU fiber particles and a silica layer in-situ deposited and grown on its outer wall. The silica content in the nano-scrubber is 52wt%; the particle size of the nano-scrubber is greater than or equal to 0.5μm and less than 1μm, the inner diameter of the hollow TPU fiber particles is 0.2-0.4μm and the wall thickness is 0.1μm, and the thickness of the silica layer is 0.1-0.2μm.

[0107] Example 3

[0108] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0109] (1) Preparation of raw materials;

[0110] TPU particles: manufacturer is Wanhua Chemical Group Co., Ltd., model number is WHT-1172IC;

[0111] N,N-dimethylacetamide;

[0112] Silicon source: ethyltriethoxysilane;

[0113] Acidic solution: a mixture of hydrochloric acid aqueous solution and acetic acid aqueous solution in a mass ratio of 1:1, and the concentration of the hydrochloric acid aqueous solution and the acetic acid aqueous solution are both 20wt%;

[0114] Alkali: calcium hydroxide;

[0115] (2) Preparation of nano-abrasives;

[0116] (2.1) dissolving TPU particles in N,N-dimethylacetamide to obtain a spinning solution with a concentration of 25%, and using a hollow fiber spinneret and a wet spinning process to perform spinning and then cutting to obtain hollow TPU fiber particles;

[0117] (2.2) Dissolve the silicon source in an acidic solution and stir at 28°C until no stratification occurs to obtain a solution A having a pH value of 3;

[0118] (2.3) adding the hollow TPU fiber particles to solution A, adding alkali, stirring and reacting at 60°C for 4 hours to obtain solution B, and post-treating solution B to obtain a nano-abrasive;

[0119] In steps (2.1) to (2.3), the mass ratio of the hollow TPU fiber particles to solution A is 2:8, and the mass of the alkali is 70% of the mass of the silicon source.

[0120] The final nano-scrubber is composed of hollow TPU fiber particles and a silica layer in-situ deposited and grown on its outer wall. The silica content in the nano-scrubber is 56wt%; the particle size of the nano-scrubber is greater than or equal to 1μm and less than 10μm, the inner diameter of the hollow TPU fiber particles is 0.4-4μm and the wall thickness is 0.1-1μm, and the thickness of the silica layer is 0.2-2μm.

[0121] Example 4

[0122] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0123] (1) Preparation of raw materials;

[0124] TPU particles: manufacturer is Wanhua Chemical Group Co., Ltd., model number is WHT-1172IC;

[0125] N,N-dimethylacetamide;

[0126] Silicon source: a mixture of ethyltriethoxysilane and sodium silicate in a mass ratio of 1:1;

[0127] Acidic solution: hydrochloric acid aqueous solution, concentration is 20wt%;

[0128] Alkali: a mixture of sodium hydroxide and potassium hydroxide in a mass ratio of 1:1;

[0129] (2) Preparation of nano-abrasives;

[0130] (2.1) dissolving TPU particles in N,N-dimethylacetamide to obtain a spinning solution with a concentration of 30%, and cutting after spinning using a hollow fiber spinneret and a wet spinning process to obtain hollow TPU fiber particles;

[0131] (2.2) Dissolve the silicon source in an acidic solution and stir at 30°C until no stratification occurs to obtain a solution A having a pH value of 4;

[0132] (2.3) adding the hollow TPU fiber particles to solution A, adding alkali, stirring and reacting at 60°C for 5 hours to obtain solution B, and post-treating solution B to obtain a nano-abrasive;

[0133] In steps (2.1) to (2.3), the mass ratio of the hollow TPU fiber particles to solution A is 2:8, and the mass of the alkali is 70% of the mass of the silicon source.

[0134] The final nano-scrubber is composed of hollow TPU fiber particles and a silica layer deposited in situ and grown on its outer wall. The silica content in the nano-scrubber is 58wt%; the particle size of the nano-scrubber is greater than or equal to 10μm and less than 20μm, the inner diameter of the hollow TPU fiber particles is 3-6μm and the wall thickness is 1.5-3μm, and the thickness of the silica layer is 2-4μm.

[0135] Example 5

[0136] A method for preparing a nano-scrub agent, the specific steps are as follows:

[0137] (1) Preparation of raw materials;

[0138] TPU particles: manufacturer is Wanhua Chemical Group Co., Ltd., model number is WHT-1172IC;

[0139] N,N-dimethylacetamide;

[0140] Silicon source: a mixture of methyltrimethoxysilane and ethyltriethoxysilane in a mass ratio of 1:1;

[0141] Acidic solution: hydrochloric acid aqueous solution, concentration is 20wt%;

[0142] Alkali: a mixture of sodium hydroxide and potassium hydroxide in a mass ratio of 1:1;

[0143] (2) Preparation of nano-abrasives;

[0144] (2.1) dissolving TPU particles in N,N-dimethylacetamide to obtain a spinning solution with a concentration of 30%, and cutting after spinning using a hollow fiber spinneret and a wet spinning process to obtain hollow TPU fiber particles;

[0145] (2.2) Dissolve the silicon source in an acidic solution and stir at 25°C until no stratification occurs to obtain a solution A having a pH value of 4;

[0146] (2.3) adding the hollow TPU fiber particles to solution A, adding alkali, stirring and reacting at 60°C for 6 hours to obtain solution B, and post-treating solution B to obtain a nano-abrasive;

[0147] In steps (2.1) to (2.3), the mass ratio of the hollow TPU fiber particles to solution A is 2:8, and the mass of the alkali is 70% of the mass of the silicon source.

[0148] The final nano-scrubber is composed of hollow TPU fiber particles and a silica layer deposited in situ and grown on its outer wall. The content of silica in the nano-scrubber is 60wt%; the particle size of the nano-scrubber is greater than or equal to 20μm and less than or equal to 25μm, the inner diameter of the hollow TPU fiber particles is 6-7μm and the wall thickness is 3-4μm, and the thickness of the silica layer is 4-5μm.

[0149] Example 6

[0150] A method for preparing an extruded high-wear-resistant and high-rebound paper film, the specific steps are as follows:

[0151] (1) Preparation of raw materials;

[0152] Raw material a and raw material c: both are composed of 65wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model number is FG720) and the balance is the nano-abrasive agent of Example 1;

[0153] Raw material b: composed of 50wt% PET, 35wt% TPU (manufacturer: Wanhua Chemical Group Co., Ltd., model: WHT-1172IC), 10wt% compatibilizer and the balance of ethylene terpolymer (manufacturer: DuPont, model: PTW). The compatibilizer is a mixture of polyolefin elastomer POE (manufacturer: DuPont, model: N216) and maleic acid rod grafted compatibilizer TPU-G-MAH (manufacturer: Dongguan Shenghao Plastic Raw Materials Co., Ltd.) in a mass ratio of 1:1;

[0154] (2) Preparation of extruded high wear-resistant and high resilience paper films;

[0155] (2.1) melt-blending and granulating raw material a to obtain modified slice a, melt-blending and granulating raw material b to obtain modified slice b, and melt-blending and granulating raw material c to obtain modified slice c;

[0156] (2.2) The modified slice a, the modified slice b, and the modified slice c are melt-extruded through an extruder, respectively, and extruded through a filter, a melt metering pump, a distributor, and a multi-layer co-extrusion die head, and cooled on a cooling roller to obtain a thick slice;

[0157] (2.3) The thick sheet is sequentially subjected to longitudinal stretching (stretching temperature is 80°C, stretching ratio is 3.6 times), transverse stretching preheating (temperature is 80°C), transverse stretching (stretching temperature is 100°C, stretching ratio is 4 times), drying and curing (temperature is 200°C), heat setting, and cooling to obtain an extruded high wear-resistant and high resilience paper film.

[0158] The final extruded high wear-resistant and high resilience paper film consists of an upper surface layer (made of raw material a), a base layer (made of raw material b) and a lower surface layer (made of raw material c) from top to bottom; the thickness of the upper surface layer and the lower surface layer are both 0.08 mm, and the thickness of the base layer is 0.2 mm; the haze of the extruded high wear-resistant and high resilience paper film is 2.3%, the tensile resilience is 96.2%, the elongation at break is 320%, the light transmittance is 92.68%, the friction resistance is 800 times, and the dynamic friction coefficient is 0.39.

[0159] Comparative Example 4

[0160] A method for preparing a paper-like film is basically the same as Example 6, except that the nano-abrasive agent in Example 1 is replaced by the nano-abrasive agent in Comparative Example 1.

[0161] The final paper-like film has a tensile resilience of 35.2%, an elongation at break of 110%, a friction resistance of 400 times, and a dynamic friction coefficient of 0.24.

[0162] Compared with Example 6, the tensile rebound rate, elongation at break, friction resistance and dynamic friction coefficient of the paper-like film in Comparative Example 4 are significantly reduced. This is because the use of hollow PP particles as the inner layer of the nano-abrasive cannot provide the paper-like film with good elasticity, and it cannot provide good support for the external silica layer and effectively disperse the external force. As a result, when the paper-like film is subjected to external force, it cannot disperse and buffer the external force well, which greatly reduces the elastic properties of the film, and further manifests itself as a significant decrease in the tensile rebound rate and elongation at break. In addition, due to poor elasticity, during the friction process, the surface of the paper-like film cannot adapt well to the pressure changes caused by friction, which weakens the friction resistance, and reduces the number of friction resistance and the dynamic friction coefficient.

[0163] Comparative Example 5

[0164] A method for preparing a paper-like film is basically the same as that of Example 6, except that the nano-abrasive agent of Example 1 is replaced by the nano-abrasive agent of Comparative Example 2.

[0165] The final paper-like film has a tensile resilience of 32.0%, an elongation at break of 92%, a friction resistance of 300 times, and a dynamic friction coefficient of 0.25.

[0166] Compared with Example 6, the tensile resilience, elongation at break, friction resistance and dynamic friction coefficient of the paper-like film in Comparative Example 5 are significantly reduced. This is because Comparative Example 5 only uses hollow silica as a nano-abrasive, which does not have the ability to effectively disperse the external force in all directions and buffer the hands when subjected to external force. As a result, the elastic properties of the paper-like film are greatly affected when subjected to external force, which is manifested in a significant decrease in the tensile resilience and elongation at break. During the friction process, due to the lack of an effective external force dispersion and buffering mechanism, the adaptability of the paper-like film surface when subjected to friction pressure becomes poor, resulting in a decrease in friction resistance, friction resistance times and dynamic friction coefficient.

[0167] Comparative Example 6

[0168] A method for preparing a paper-like film is basically the same as that of Example 6, except that the nano-abrasive agent of Example 1 is replaced by the nano-abrasive agent of Comparative Example 3.

[0169] The final paper-like film has a tensile resilience of 30.1%, an elongation at break of 81%, a friction resistance of 300 times, and a dynamic friction coefficient of 0.12.

[0170] Compared with Example 6, the tensile resilience, elongation at break, friction resistance and dynamic friction coefficient of the paper-like film in Comparative Example 6 are significantly reduced. This is because the nano-abrasive agent used in Comparative Example 6 is solid silica, which has neither a double-layer airbag structure nor elasticity. When the paper-like film is subjected to external force, it cannot buffer the influence of the external force on the film well, causing the elastic properties of the film to drop sharply, which is manifested in a significant decrease in the tensile resilience and elongation at break. During the friction process, due to the lack of an effective external force dispersion and buffering mechanism, the adaptability of the paper-like film surface when subjected to friction pressure is very poor, resulting in a decrease in friction resistance, friction resistance times and dynamic friction coefficient.

[0171] Example 7

[0172] A method for preparing an extruded high-wear-resistant and high-rebound paper film is basically the same as Example 6, except that: raw material a and raw material c are both composed of 65wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model FG720) and the remainder of a nano-abrasive composition, and the nano-abrasive composition is composed of 30wt% of the nano-abrasive of Example 1, 25wt% of the nano-abrasive of Example 2, 20wt% of the nano-abrasive of Example 3, 15wt% of the nano-abrasive of Example 4, and 10wt% of the nano-abrasive of Example 5.

[0173] The final extruded high-wear-resistant and high-resilient paper film has a haze of 2.7%, a tensile rebound rate of 99.8%, an elongation at break of 351%, a light transmittance of 92.75%, a friction resistance of 1600 times, and a dynamic friction coefficient of 0.46.

[0174] Example 8

[0175] A method for preparing an extruded high-wear-resistant and high-rebound paper film, the specific steps are as follows:

[0176] (1) Preparation of raw materials;

[0177] Raw material a and raw material c: both are composed of 85wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model number is FG720) and the balance is the nano-abrasive agent of Example 2;

[0178] Raw material b: composed of 62wt% PET, 30wt% TPU (manufacturer: Wanhua Chemical Group Co., Ltd., model: WHT-1172IC), 5wt% polyolefin elastomer POE (manufacturer: DuPont, USA, model: N216) and the balance ethylene terpolymer (manufacturer: DuPont, USA, model: PTW);

[0179] (2) Preparation of extruded high wear-resistant and high resilience paper films;

[0180] (2.1) melt-blending and granulating raw material a to obtain modified slice a, melt-blending and granulating raw material b to obtain modified slice b, and melt-blending and granulating raw material c to obtain modified slice c;

[0181] (2.2) The modified slice a, the modified slice b, and the modified slice c are melt-extruded through an extruder, respectively, and extruded through a filter, a melt metering pump, a distributor, and a multi-layer co-extrusion die head, and cooled on a cooling roller to obtain a thick slice;

[0182] (2.3) The thick sheet is sequentially subjected to longitudinal stretching (stretching temperature is 100°C, stretching ratio is 3 times), transverse stretching preheating (temperature is 120°C), transverse stretching (stretching temperature is 130°C, stretching ratio is 3.1 times), drying and curing (temperature is 240°C), heat setting, and cooling to obtain an extruded high wear-resistant and high resilience paper film.

[0183] The final extruded high wear-resistant and high resilience paper film consists of an upper surface layer (made of raw material a), a base layer (made of raw material b) and a lower surface layer (made of raw material c) from top to bottom; the thickness of the upper surface layer and the lower surface layer are both 1.2 mm, and the thickness of the base layer is 0.24 mm; the haze of the extruded high wear-resistant and high resilience paper film is 2.1%, the tensile resilience is 96.9%, the elongation at break is 331%, the light transmittance is 94.92%, the friction resistance is 900 times, and the dynamic friction coefficient is 0.4.

[0184] Example 9

[0185] A method for preparing an extruded high-wear-resistant and high-rebound paper film is basically the same as Example 8, except that: raw material a and raw material c are both composed of 85wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model FG720) and the remainder of a nano-abrasive composition, and the nano-abrasive composition is composed of 50wt% of the nano-abrasive of Example 1, 20wt% of the nano-abrasive of Example 2, 15wt% of the nano-abrasive of Example 3, 10wt% of the nano-abrasive of Example 4, and 5wt% of the nano-abrasive of Example 5.

[0186] The final extruded high-wear-resistant and high-resilient paper film has a haze of 2.5%, a tensile rebound rate of 98.5%, an elongation at break of 342%, a light transmittance of 95.55%, a friction resistance of 1500 times, and a dynamic friction coefficient of 0.44.

[0187] Example 10

[0188] A method for preparing an extruded high-wear-resistant and high-rebound paper film, the specific steps are as follows:

[0189] (1) Preparation of raw materials;

[0190] Raw material a and raw material c: both are composed of 85wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model number is FG720) and the balance is the nano-abrasive agent of Example 3;

[0191] Raw material b: composed of 62wt% PET, 30wt% TPU (manufacturer: Wanhua Chemical Group Co., Ltd., model: WHT-1172IC), 5wt% maleic acid rod grafted compatibilizer TPU-G-MAH (manufacturer: Dongguan Shenghao Plastic Raw Materials Co., Ltd.) and the balance ethylene terpolymer (manufacturer: DuPont, USA, model: PTW);

[0192] (2) Preparation of extruded high wear-resistant and high resilience paper films;

[0193] (2.1) melt-blending and granulating raw material a to obtain modified slice a, melt-blending and granulating raw material b to obtain modified slice b, and melt-blending and granulating raw material c to obtain modified slice c;

[0194] (2.2) The modified slice a, the modified slice b, and the modified slice c are melt-extruded through an extruder, respectively, and extruded through a filter, a melt metering pump, a distributor, and a multi-layer co-extrusion die head, and cooled on a cooling roller to obtain a thick slice;

[0195] (2.3) The thick sheet is sequentially subjected to longitudinal stretching (stretching temperature is 100°C, stretching ratio is 3 times), transverse stretching preheating (temperature is 120°C), transverse stretching (stretching temperature is 130°C, stretching ratio is 3.1 times), drying and curing (temperature is 240°C), heat setting, and cooling to obtain an extruded high wear-resistant and high resilience paper film.

[0196] The final extruded high wear-resistant and high resilience paper film consists of an upper surface layer (made of raw material a), a base layer (made of raw material b) and a lower surface layer (made of raw material c) from top to bottom; the thickness of the upper surface layer and the lower surface layer are both 1.2 mm, and the thickness of the base layer is 0.24 mm; the haze of the extruded high wear-resistant and high resilience paper film is 2.5%, the tensile resilience is 96.7%, the elongation at break is 328%, the light transmittance is 93.68%, the friction resistance is 1000 times, and the dynamic friction coefficient is 0.41.

[0197] Embodiment 11

[0198] A method for preparing an extruded high-wear-resistant and high-rebound paper film, the specific steps are as follows:

[0199] (1) Preparation of raw materials;

[0200] Raw material a and raw material c: both are composed of 85wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model number is FG720) and the balance is the nano-abrasive agent of Example 4;

[0201] Raw material b: composed of 62wt% PET, 30wt% TPU (manufacturer: Wanhua Chemical Group Co., Ltd., model: WHT-1172IC), 5wt% compatibilizer and the balance of ethylene terpolymer (manufacturer: DuPont, model: PTW). The compatibilizer is a mixture of polyolefin elastomer POE (manufacturer: DuPont, model: N216) and maleic acid rod grafted compatibilizer TPU-G-MAH (manufacturer: Dongguan Shenghao Plastic Raw Materials Co., Ltd.) in a mass ratio of 1:1;

[0202] (2) Preparation of extruded high wear-resistant and high resilience paper films;

[0203] (2.1) melt-blending and granulating raw material a to obtain modified slice a, melt-blending and granulating raw material b to obtain modified slice b, and melt-blending and granulating raw material c to obtain modified slice c;

[0204] (2.2) The modified slice a, the modified slice b, and the modified slice c are melt-extruded through an extruder, respectively, and extruded through a filter, a melt metering pump, a distributor, and a multi-layer co-extrusion die head, and cooled on a cooling roller to obtain a thick slice;

[0205] (2.3) The thick sheet is sequentially subjected to longitudinal stretching (stretching temperature is 100°C, stretching ratio is 3 times), transverse stretching preheating (temperature is 120°C), transverse stretching (stretching temperature is 130°C, stretching ratio is 3.1 times), drying and curing (temperature is 240°C), heat setting, and cooling to obtain an extruded high wear-resistant and high resilience paper film.

[0206] The final extruded high wear-resistant and high resilience paper film consists of an upper surface layer (made of raw material a), a base layer (made of raw material b) and a lower surface layer (made of raw material c) from top to bottom; the thickness of the upper surface layer and the lower surface layer are both 1.2 mm, and the thickness of the base layer is 0.24 mm; the haze of the extruded high wear-resistant and high resilience paper film is 2.6%, the tensile resilience is 97.2%, the elongation at break is 338%, the light transmittance is 92.69%, the friction resistance is 1100 times, and the dynamic friction coefficient is 0.42.

[0207] Example 12

[0208] A method for preparing an extruded high-wear-resistant and high-rebound paper film, the specific steps are as follows:

[0209] (1) Preparation of raw materials;

[0210] Raw material a and raw material c: both are composed of 85wt% of PET (manufacturer is Sinopec Yizheng Chemical Fiber Co., Ltd., model number is FG720) and the balance is the nano-abrasive agent of Example 5;

[0211] Raw material b: composed of 62wt% PET, 30wt% TPU (manufacturer: Wanhua Chemical Group Co., Ltd., model: WHT-1172IC), 5wt% compatibilizer and the balance of ethylene terpolymer (manufacturer: DuPont, model: PTW). The compatibilizer is a mixture of polyolefin elastomer POE (manufacturer: DuPont, model: N216) and maleic acid rod grafted compatibilizer TPU-G-MAH (manufacturer: Dongguan Shenghao Plastic Raw Materials Co., Ltd.) in a mass ratio of 1:1;

[0212] (2) Preparation of extruded high wear-resistant and high resilience paper films;

[0213] (2.1) melt-blending and granulating raw material a to obtain modified slice a, melt-blending and granulating raw material b to obtain modified slice b, and melt-blending and granulating raw material c to obtain modified slice c;

[0214] (2.2) The modified slice a, the modified slice b, and the modified slice c are melt-extruded through an extruder, respectively, and extruded through a filter, a melt metering pump, a distributor, and a multi-layer co-extrusion die head, and cooled on a cooling roller to obtain a thick slice;

[0215] (2.3) The thick sheet is sequentially subjected to longitudinal stretching (stretching temperature is 100°C, stretching ratio is 3 times), transverse stretching preheating (temperature is 120°C), transverse stretching (stretching temperature is 130°C, stretching ratio is 3.1 times), drying and curing (temperature is 240°C), heat setting, and cooling to obtain an extruded high wear-resistant and high resilience paper film.

[0216] The final extruded high wear-resistant and high resilience paper film consists of an upper surface layer (made of raw material a), a base layer (made of raw material b) and a lower surface layer (made of raw material c) from top to bottom; the thickness of the upper surface layer and the lower surface layer are both 1.2 mm, and the thickness of the base layer is 0.24 mm; the haze of the extruded high wear-resistant and high resilience paper film is 2.7%, the tensile resilience is 98.2%, the elongation at break is 340%, the light transmittance is 92.71%, the friction resistance is 1200 times, and the dynamic friction coefficient is 0.45.

Claims

1. A nano-abrasive agent, characterized in that: It consists of hollow TPU fiber particles and a silicon dioxide layer deposited and grown in situ on its outer wall.

2. A nano-abrasive agent according to claim 1, characterized in that: The content of silicon dioxide in the nano-abrasive is 50-60wt%.

3. A nano-abrasive agent according to claim 2, characterized in that: The particle size of the nano-abrasive is less than 0.5 μm, the inner diameter of the hollow TPU fiber particles is 0.1-0.2 μm and the wall thickness is 0.05 μm, and the thickness of the silicon dioxide layer is 0.05-0.1 μm.

4. A nano-abrasive agent according to claim 2, characterized in that: The particle size of the nano-abrasive is greater than or equal to 0.5 μm and less than 1 μm, the inner diameter of the hollow TPU fiber particles is 0.2-0.4 μm and the wall thickness is 0.1 μm, and the thickness of the silicon dioxide layer is 0.1-0.2 μm.

5. A nano-abrasive agent according to claim 2, characterized in that: The particle size of the nano-abrasive is greater than or equal to 1 μm and less than 10 μm, the inner diameter of the hollow TPU fiber particles is 0.4-4 μm and the wall thickness is 0.1-1 μm, and the thickness of the silicon dioxide layer is 0.2-2 μm.

6. A nano-abrasive agent according to claim 2, characterized in that: The particle size of the nano-abrasive agent is greater than or equal to 10 μm and less than 20 μm, the inner diameter of the hollow TPU fiber particles is 3-6 μm and the wall thickness is 1.5-3 μm, and the thickness of the silicon dioxide layer is 2-4 μm.

7. The nano-abrasive agent according to claim 2, characterized in that: The particle size of the nano-abrasive agent is greater than or equal to 20 μm and less than or equal to 25 μm, the inner diameter of the hollow TPU fiber particles is 6-7 μm and the wall thickness is 3-4 μm, and the thickness of the silicon dioxide layer is 4-5 μm.

8. A nano-scrub composition, characterized in that: It is composed of 30-50wt% of a nano-abrasive as claimed in claim 3, 20-25wt% of a nano-abrasive as claimed in claim 4, 15-20wt% of a nano-abrasive as claimed in claim 5, 10-15wt% of a nano-abrasive as claimed in claim 6, and 5-10wt% of a nano-abrasive as claimed in claim 7.

9. A method for preparing a nano-abrasive agent as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (a) Preparation of hollow TPU fiber particles; (b) dissolving a silicon source in an acidic solution to obtain a solution A; (c) The hollow TPU fiber particles are added to solution A, and after adding alkali, the mixture is reacted at 60° C. for 2-6 hours under stirring to obtain solution B, and solution B is post-treated to obtain a nano-abrasive.

10. An extruded high wear-resistant and high resilience paper film, characterized in that: It comprises an upper surface layer, a base layer and a lower surface layer arranged in sequence from top to bottom; the upper surface layer and the lower surface layer contain additives, and the additives are a nano-scrubber as described in any one of claims 1 to 7 or a nano-scrubber composition as described in claim 8.

Citation Information

Patent Citations

  • High-elasticity and high-abrasion-resistance TPU composite fabric and preparing method thereof

    CN105150616A

  • Anti-fingerprint TPU (thermoplastic polyurethane) protective film

    CN109554133A

  • Nanoparticle-coated elastomeric particulates and methods for production and use thereof

    CN112457671A

  • High-wear-resistance paper film as well as preparation method and application thereof

    CN118290801A

  • Novel SiO2 carrier material and use in polyolefin catalyst and its preparing method

    CN1781997A